Learner Variables in Second Language Listening Comprehension: An Exploratory Path Analysis. Issue 2 (June 2015) - Vandergrift, Larry; Baker, Susan
<x xml:space="preserve">Abstract</x> Listening comprehension plays a key role in language acquisition, yet little is known about the variables that contribute to the development of second language (L2) listening ability. This study sought to obtain empirical evidence for the impact of some of the learner variables and the degree to which they might predict success in L2 listening. The learner variables of interest included: first language (L1) listening ability, L1 vocabulary knowledge, L2 vocabulary knowledge, auditory discrimination ability, metacognitive awareness of listening, and working memory capacity. Data from 157 Grade Seven students in the first year of a French immersion program indicated a significant relationship among most of the variables and L2 listening ability. A number of path analyses were then conducted, based on hypothetical relationships suggested by current theory and research, in order to uncover relationships between the variables in determining L2 listening comprehension ability. The best fit to the data supported a model in which general skills (auditory discrimination and working memory) are initially important, leading to more specific language skills (L1 and L2 vocabulary) in determining L2 listening comprehension. In positing a provisional model, this study opens up useful avenues for further research on model building in L2 listening.